Reconfiguration of space in the knowledge society - Kujath, Hans Joachim; Stein, Axel (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
Since long knowledge has been a motor for the society’s development. The way knowledge is produced, distributed, and applied, has changed considerably and leads to regional differences. In this article the spatial implications of this development are theoretically, statistically, and empirically elaborated. The spatial dimension of the knowledge society becomes apparent by the identification of, firstly, types of spaces and locations and, secondly, the resulting spatial patterns. Finally, the consequences for development strategies are discussed, namely in relation to knowledge society’s location factors and the pooling of knowledge networks in knowledge regions.